Follicular Growth and Atresia in Mammalian Ovaries: Regulation by Survival and Death of Granulosa Cells - MATSUDA, Fuko; INOUE, Naoko; MANABE, Noboru; OHKURA, Satoshi (Journal of Reproduction and Development, 2012)
The mammalian ovary is an extremely dynamic organ in which a large majority of follicles are effectively eliminated throughout their reproductive life. Due to the numerous efforts of researchers, mechanisms regulating follicular growth and atresia in mammalian ovaries have been clarified, not only their systemic regulation by hormones (gonadotropins) but also their intraovarian regulation by gonadal steroids, growth factors, cytokines and intracellular proteins. Granulosa cells in particular have been demonstrated to play a major role in deciding the fate of follicles, serving molecules that are essential for follicular growth and maintenance as well as killing themselves by an apoptotic process that results in follicular atresia. In this review, we discuss the factors that govern follicular growth and atresia, with a special focus on their regulation by granulosa cells. First, ovarian folliculogenesis in adult life is outlined. Then, we explain about the regulation of follicular growth and atresia by granulosa cells, in which hormones, growth factors and cytokines, death ligand-receptor system and B cell lymphoma/leukemia 2 (BCL2) family members (mitochondria-mediated apoptosis) are further discussed.